Folic acid flour fortification: Impact on the frequencies of 52 congenital anomaly types in three South American countries - López Camelo, Jorge Santiago (2010)
The aim of the present investigation was to search for a reduction in birth prevalence estimates of 52 selected types of congenital anomalies, associated with folic acid fortification programs in Chile, Argentina, and Brazil. The material included 3,347,559 total births in 77 hospitals of the three countries during the 1982-2007 period: 596,704 births (17 hospitals) in Chile, 1,643,341 (41 hospitals) in Argentina, and 1,107,514 (19 hospitals) in Brazil. We compared pre- and post-fortification rates within each hospital and the resulting Prevalence Rate Ratios (PRRs) were pooled by country. Statistically significant reductions in birth prevalence estimates after fortification were observed for neural tube defects (NTDs), septal heart defects, transverse limb deficiencies, and subluxation of the hip. However, only the reduction of NTDs appeared to be associated with folic acid fortification and not due to other factors, because of its consistency among the three countries, as well as with previously published reports, and its strong statistical significance. Among the NTDs, the maximum prevalence reduction was observed for isolated cephalic (cervical-thoracic) spina bifida, followed by caudal (lumbo-sacral) spina bifida, anencephaly, and cephalocele. This observation suggests etiologic and pathogenetic heterogeneity among different levels of spina bifida, as well as among different NTD subtypes. We concluded that food fortification with folic acid prevents NTDs but not other types of congenital anomalies.